Social and Environmental Mechanisms of Management in Agri-Business - BARBAKOV, Oleg M.; GERASIMOVA, Galina A.; PEZIN, Dmitry A. (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019DO - 10.14505//jemt.v10.3(35).20, 2019)
Existing technologies and technological processes in production areas in the overwhelming majority are open systems in which natural resources are inefficiently used and significant waste is generated. Irrational water use and environmental degradation in traditional irrigation zones necessitate an analysis of the problems of environmental assessment and the applicability of irrigation systems, which makes this study relevant. The article aims to develop a methodology for assessing the technological process in agrolandscape systems from the point of view of resource conservation, ensuring strict regulation of environmentally friendly and waste-free technology and technological schemes for irrigating crops. The main principles of non-waste production process technologies are used. On the basis of them, a system of integral criteria for assessing the environmental reliability of irrigation technology and irrigation systems is presented, which allows creating an environmentally safe resource-saving technological process in agrolandscape systems. It was concluded that the task of managing the agro-industrial complex should be the creation of environmentally sustainable agricultural landscapes. The results of the study can be the basis for the formation of sustainable management decisions in the management of the agro-industrial complex from the standpoint of resource saving.